KOMUNIKASI BUDAYA: SUATU TINJAUAN ANTROPOLOGI PENGGUNAAN TANGAN KIRI PADA MASYARAKAT DI SEKITAR KAMPUS PERAK - Abdul Jalil (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
The phenomenon of left hand use (which is culturally unusual) by the community around the Campus Perak urges the authors explore its background from the cultural approach in an ethnographic study. There had been some community practices around Campus Perak in Southeast Sulawesi that are considered as anomalies by outsiders' perspectives. Among those anomalies is the use of the left hand in giving something to others, such as serving food, writing, and signing letters. This paper explores the use of the left hand amidst the society around the Perak Campus. In general, several ethnic groups inhabit the area around campus, thus no particular ethnic dominates the use of everyday language. Tribal languages are commonly used among people from the similar ethnicity. In the context offormal ceremonies involving community outside Campus Perak, the use of left hand was seen as a culture shock. Meanwhile, the use of left hand was (intra)culturally acceptable since children were taught using left hands by their parents. KEY WORDS: Left Hand, Cultural Communication, Campus Perak, Society